MODEL PENGEMBANGAN MAKANAN DAN PARIWISATA HALAL DI INDONESIA - Menur Kusumaningtyas; Sri Lestari (Media Mahardhika, 2020)
This paper discusses the issue of developing halal food and its role in halal tourism in Indonesia to be more competitive with other Muslim countries. This study aims to explore the role of government and the Muslim community in general in the development of halal food and tourism in Indonesia. The research method used is descriptive qualitative literature review. Based on the results of the analysis obtained the hypothesis that the role of government in the application of halal certification is very influential on the level of consumptive tourists. Indonesia with a Muslim majority population must be able to become a halal industry producer which is currently still dominated by countries with Muslim minorities such as Australia, New Zealand, Brazil and even small countries like Singapore. Examining government regulations related to tourism and halal food will provide enlightenment on the importance of stretching halal tourism destinations with halal food offerings in Indonesia.